The effect of perforations on built-up open section cold-formed steel beam - Siti Sharina, Baharom (2018)
This paper presents the study of the effect on built-up open section when receiving load in term of flexural behavior (failure mode) and the ultimate load with the present of web perforations. In steel production, there are two types of structural members which are hotrolled steel and the other one is cold-formed steel. In detail, cold-formed steel is pressed at significantly cooler temperatures and often even room temperature. Hot-rolled steel is heated above the metal recrystallization temperature (around 1700° F or higher) to make it easier to bend the metal into specific shape. This experiment is involving the beam test on several specimens focuses on built-up open section steel with various position of webopening on the beam. Each specimen have 1600 mm length and different position of webperforations. The shape of openings used are circle and the size are keep constant that is 20 mm diameter to ensure the consistency in the result making. The ultimate load strength of the cold-formed steel section and failure modes differs depend on the position of the openings and the number of the opening, where the conclusions are make on the basis of the comparisons between the positions of openings. The value of displacement was measured by using the transducer which placed at the middle point below the beam. The load – displacement graph was plotted after the result is obtained.